2016
DOI: 10.1515/rrlm-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional modifications in biathlon athletes at medium altitude training / Modificările biochimice și funcționale ale atleților biatloniști după antrenament la altitudine medie

Abstract: Objective: The aim of our research was to identify physiological and biochemical changes induced by training at medium altitude. Methods: Ten biathlon athletes underwent 28-day training camp at medium altitude in order to improve their aerobic effort, following the living high-base train high-interval train low (Hi-Hi-Lo) protocol. There were investigated three categories of functional and biochemical parameters, targeting the hematological changes (RBC, HCT, HGB), the oxidative (lipoperoxid, free malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An elevated muscle temperature usually occurs from the friction of intramuscular movement that occurs during exercise. When the muscle temperature is higher, it results in the increased transmission rate of an impulse, which is responsible for all our movement in exercise, and this will positively affect the force–velocity relationship, which is the core of performance output [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated muscle temperature usually occurs from the friction of intramuscular movement that occurs during exercise. When the muscle temperature is higher, it results in the increased transmission rate of an impulse, which is responsible for all our movement in exercise, and this will positively affect the force–velocity relationship, which is the core of performance output [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the long term, training that applies apnea exercises improves the duration of maintenance, but also increases the tolerance to hypoxia [27]. The approach to sports training must be made in an interdisciplinary way so as to identify how different specific factors contribute to improving sports performance [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that plateau or hypoxic training enhances aerobic metabolism and promotes anaerobic metabolism ( Bădău et al, 2016 ; Christoulas, Karamouzis & Mandroukas, 2011 ; Holmberg, 2015 ). Hypoxia can induce the expression of HIF-1 and HIF-1-related genes ( Cimino et al, 2012 ; Yeo, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is less research on the physical functional status of athletes in skill-led or speed-led snowboarding sports such as the snowboarding parallel giant slalom, snowboarding U-course tricks, snowboarding slopestyle tricks, snowboarding big jump, and snowboarding obstacle chase. Numerous studies have found that altitude training significantly increases the red blood cell and hemoglobin levels of cross-country skiers and biathletes, which, in turn, promotes higher maximum oxygen uptake and improved performance ( Bădău et al, 2016 ; Christoulas, Karamouzis & Mandroukas, 2011 ; Sandbakk & Holmberg, 2017 ; Wehrlin, Marti & Hallen, 2016 ). In view of the specificity of the oxygen-deficient cold environment of the altitude in winter, it is not known how these conditions affect the physical functional status and athletic ability of athletes.…”
Section: Introductionmentioning
confidence: 99%